Exploring bosonic mediator of interaction at BESIII - Jun Jiang; Hao Yang; Cong-Feng Qiao (European Physical Journal C: Particles and Fields, 2019)
Abstract We present a comprehensive investigation on the possibility of the search for new force mediator X boson in $$e^+e^-$$ e+e- collision and $$J/\psi $$ J/ψ decay at the BESIII experiment. The typical interactions of X boson coupling to leptons and quarks are explored. The production and decay properties of this X particle, the product/decay chains $$e^+e^-\rightarrow X\gamma \rightarrow e^+e^-\gamma $$ e+e-→Xγ→e+e-γ and $$J/\psi \rightarrow X\gamma \rightarrow \mu ^+\mu ^-\gamma $$ J/ψ→Xγ→μ+μ-γ , and exclusion limits on the reduced coupling strength parameters as functions of X boson mass are presented. With the data set of tens of $$\hbox {fb}^{-1}~e^+e^-$$ fb-1e+e- or $$10^{10}~J/\psi $$ 1010J/ψ , we find that the exclusion limits on the coupling strength parameters fall in the range of $$10^{-3}\sim 10^{-4}$$ 10-3∼10-4 , depending on $$m_X$$ mX assuming the decay width 10 eV$$<\Gamma _X<$$ <ΓX< 100 eV reasonably, for various hypotheses in the literature. According to our estimation, the search for new force mediator X boson in both $$e^+e^-$$ e+e- collision and $$J/\psi $$ J/ψ decay are accessible in nowadays BESIII experiment.